Strategi Guru dalam Meningkatkan Minat Belajar Agama Islam Siswa Kelas V SD Kreatif Rusyda - Nurmayani Nurmayani; Dira Supratiwi; Annisa Hapsari; Dwi Rahmi Anissa Tanjung; Fazira Nazwa; Nesa Andari; Syazilla Machreni (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study highlights the crucial role of learning interest as a key determinant of success in the educational process. The research was conducted through interviews with teachers and direct observations in the learning environment, aiming to explore how various factors influence students’ interest, particularly in religious education. The findings indicate that teachers play an essential role by adopting creative approaches in their teaching methods. For instance, the integration of digital tools, such as instructional videos, was found to be highly effective in capturing students’ attention and enhancing their engagement during lessons. Furthermore, parental support emerged as a significant factor, as parents act as the first educators at home by instilling fundamental religious values and attitudes that shape students’ motivation. The results also suggest that a positive classroom atmosphere, where students feel appreciated and supported by their teachers, contributes to higher levels of interest and participation in religious studies. In addition, the study emphasizes the importance of differentiated instruction, where tasks are adjusted to match students’ abilities and learning needs. By connecting lesson materials with real-life experiences, teachers can further foster students’ intrinsic motivation, making learning more meaningful and relevant. Overall, the research demonstrates that cultivating interest in learning requires collaboration between teachers, parents, and supportive learning environments.